Single-Cell Multiomic Approaches Reveal Diverse Labeling of the Nervous System by Common Cre-Drivers - Keuls, Rachel A.; Parchem, Ronald J. (Frontiers in Cellular Neuroscience, 2021)
Abstract Neural crest development involves a series of dynamic, carefully coordinated events that result in human disease when not properly orchestrated. Cranial neural crest cells acquire unique multipotent developmental potential upon specification to generate a broad variety of cell types. Studies of early mammalian neural crest development and nervous system development often use the Cre-loxP system to lineage trace and mark cells for further investigation. Here we carefully profile the activity of two common neural crest Cre-drivers at the end of neurulation in mice. RNA sequencing of labeled cells at E9.5 reveals that Wnt1-Cre2 marks cells with neuronal characteristics consistent with neuroepithelial expression, whereas Sox10-Cre predominantly labels the migratory neural crest. We used single-cell mRNA and single-cell ATAC sequencing to profile expression of Wnt1 and Sox10 and identify transcription factors that may regulate expression of Wnt1-Cre2 in the neuroepithelium and Sox10-Cre in migratory neural crest. Our data identify cellular heterogeneity during cranial neural crest development and identify specific populations labeled by two Cre-drivers in the developing nervous system.